En face mode of swept-source optical coherence tomography in circumscribed choroidal haemangioma. Issue 3 (23rd July 2015) - Flores-Moreno, Ignacio; Caminal, Josep M; Arias-Barquet, Luis; Rubio-Caso, Marcos J; Catala-Mora, Jaume; Vidal-Martí, María; Muñoz-Blanco, Alex; Filloy, Alejandro; Ruiz-Moreno, José M; Duker, Jay S; Arruga, Jorge
Abstract : Purpose: To describe the findings in circumscribed choroidal haemangioma (CCH) using en face swept-source optical coherence tomography (SS-OCT). Methods: En face images were obtained employing DRI-1 Atlantis OCT (Topcon, Tokyo, Japan), using a three-dimensional volumetric scan of 12×9 mm. Images were obtained from the retinal pigment epithelium to 1000 μm in depth of the tumour. Results: Twenty-two eyes from 22 patients with the clinical diagnosis of CCH were included. In 20 eyes (90.9%), a characteristic pattern was visualised in the en face image across the vascular tumour. A multilobular pattern, similar to a honeycomb, with hyporeflective, confluent, oval or round areas corresponding with the lumen of the tumour vascular spaces, and hyper-reflective zones, which may represent the vessels walls and connective tissue of the tumour. Ten eyes (45.4%) showed a hyper-reflective halo surrounding the tumour. Seventeen tumours (77.2%) showed small diameter vessels at the inner zone and larger vessels in the outer area. Twelve patients (54.5%) had previously received treatment (photodynamic therapy, transpupillary thermotherapy, dexamethasone intravitreal implant or brachytherapy with ruthenium-106). No differences were found between treated and untreated patients in any of the measured parameters. Conclusions: En face SS-OCT is a rapid, non-invasive, high-resolution, technology, which allows a complementary study to cross-sectional scans in CCH. A characteristic multilobular pattern, with a hyper-reflective halo surrounding the tumour, was found in en face SS-OCT images. No morphological differences were found between naïve patients and patients who received previous treatment.